Determining the Optimal Longitudinal Spacing Between Upper and Lower Working Elements in Two-Tier Chisel-Type Plows (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This scientific paper presents a complete methodology for determining the optimal longitudinal spacing between the lower deep-loosening shanks and the upper working tools of two-tier chisel-type plows. The study integrates soil deformation modeling, traction resistance optimization, analytical formulas, and IMRaT structural requirements. Results show that proper spacing significantly improves soil loosening, reduces traction demand, and enhances soil physical properties. Analytical formulas and engineering guidelines for real-world design and calibration are provided.